(untitled) (South East Asia Journal of Public Health, 2013)
Health promotion is the process of enabling people to increase control over and to improve their health and is emerging as a critical domain of public health. Over the last two decades, the medical model of health care, with its reliance upon clinically oriented experts, has begun a subtle shift that highlights towards a participatory model of health promotion emphasizing healthful lifestyles and healthy communities. This health promotion movement demands public health professionals to create alliances with other disciplines which would ultimately strengthen a holistic model of health as envisaged by World Health Organization. Health promotion encompasses five key strategies with health communication and education as cornerstones. Although developed countries have incorporated health promotion activities as an integral component of their public health system and initiated health promotion education systematically, developing countries are yet to adopt the same. The present paper attempts to explore the importance of health promotion as a core discipline and tool in advancing public health education, research and practice. It further illustrates few health promotion models that have been adopted and practiced for community health development. The paper advocates for stronger recognition health promotion as an integral entity and incorporation of health promotion in all domains of public health. South East Asia J Public Health | Jan-June 2012 | Vol 2 Issue 1 | 3-7 DOI: http://dx.doi.org/10.3329/seajph.v2i1.15253